A preliminary study on the variability of blood glucose following meal consumption as it relates to differences in oral glucose tolerance in young adults. Issue 3 (July 2013) - Hopper, Mari K; Koch, Carynn E; Koch, Jenny L
Insulin resistance (IR) affects the ability to maintain normal glycemia and places one at greater risk of the development of disease. The aim of this study was to assess IR via the administration of an oral glucose tolerance test (OGTT) and then determine the relationship between IR and postprandial blood glucose levels in young adults 19–24 years of age. Following a 10 hour fast, 10 men and 10 women completed an OGTT and in three subsequent weeks consumed high, medium, and low glycemic load (GL) meals in random order. Fasted and two-hour (2 h) blood glucose levels were determined. Height, weight, and waist circumference were measured and subjects completed a questionnaire recording recent weight gain, family history of diabetes, and physical fitness. Although all fasted blood glucose levels were normal, two subjects classified as impaired glucose tolerant based on 2 h OGTT values >140 mg/dL. OGTT and high glycemic load meal 2 h blood glucose levels were highly significantly correlated ( p = 0.0012). Significantly higher blood glucose levels were also found in women, high BMI, low fitness, and rapid weight gain groups. Although limited by a small sample, these preliminary data suggest that glycemic response to meal ingestion is based on both the GL of the meal and the individual's level of IR.